Intelligent Glasses, Watches and Vests...Oh My! Rethinking the Meaning of "Harm" in the Age of Wearable Technologies - Jadad, Alejandro R; Fandiño, Marcela; Lennox, Robin (JMIR Publications, 2015)
The widespread release and adoption of wearable devices will likely accelerate the "hybrid era", already initiated by mobile digital devices, with progressively deeper levels of human-technology co-evolution and increasing blurring of our boundaries with machines. Questions about the potentially harmful nature of information and communication technologies have been asked before, since the introduction of the telephone, the Web, and more recently, mobile phones. Our capacity to answer them now is limited by outdated conceptual approaches to harm, mostly derived from drug evaluation; and by the slow and static nature of traditional research tools. In this article, we propose a re-conceptualizing of the meaning of "harm", which builds on a global effort focused on health, adding flexibility and richness within a context that acknowledges the physical, mental, and social domains in which it can occur.